Crustal inhomogeneities of Bransfield Strait (West Antarctiсa). New geophysical data - Levashov, S.; Korchagin, I.; Kozlenko, Yu.; Solovyov, V. (Український антарктичний журнал, 2006)
The Ukrainian Antarctic expeditions provided new geophysical data for many West Antarctica bottom structures. Gravity, magnetic- and electromagnetic surveys near the Antarctic Peninsula enabled to specify the age of the formation of some blocks, separate local crustal inhomogeneities of Bransfield Strait and continental margin of Antarctica. The similar results obtained by three different methods assure the notable magmatic activity of Bransfield Trough that forms in the conditions of structural transformations and rifting processes migrating NE-SW war along Bransfield Strait. It is quite probable that this area is dominated by diffusion tension process but not by the expansion of a mid-oceanic ridge in a back of a volcanic arc.